The Diffusion of Military Technology. Issue 6 (19th September 2018) - Schmid, Jon
Abstract: The impact of national defense research and development spending on overall innovation depends on the extent to which the knowledge and technologies generated by defense funding diffuse. This article uses an original data-set of patents assigned to defense-servicing organizations to investigate the diffusion of military technologies. Contrary to the predictions of the prevailing scholarship, I find no difference in the rate of diffusion between civilian and military technologies. Neither do military technologies assigned to government agencies diffuse at different rates than those assigned to firms. The overall technological experience of the patent assignee is found to be a positive predictor of the diffusion of military technologies. The effect of the prevailing intellectual property rights regime is ambivalent: when US patents are included in the sample, the effect of patent protection is positive, when the US is excluded, the effect is either non-significant or negative depending on the model specification that is utilized.